Employee Performance Analysis Based on Employee Competencies, Work Facilities, and Organizational Climate - Fakihudin, Wahyu; Prasetyo, Heru Eko (Faculty of Economics and Business UNTAG Semarang, 2023)
This study aims to analyze the influence of employee competency, organizational climate, and career development on the performance of PT employees. Sango Ceramic Semarang. The population in this study was 103 employees of the warehouse division at PT Sango Ceramics Indonesia. The sample in this study was 82 respondents using the proportional random sampling method. The results of this research show that employee competency, work facilities, and organizational climate have a positive and significant influence on employee performance.